Intestinal microbiota-derived short-chain fatty acids regulation of immune cell IL-22 production and gut immunity - Wenjing Yang (Nature Portfolio, 2020)
Intestinal IL-22 has important regulatory effects on the barrier and intestinal diseases and its production is controlled by the intestinal microbiome. Here the authors show that intestinal immune cell production of IL-22 is regulated by short chain fatty acids via an aryl hydrocarbon receptor and HIF1α-mediated mechanism that protects mice from intestinal inflammation.